Novel Gene Abnormality in Epilepsy with Myoclonic-Atonic Seizures (Doose Syndrome) (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Introduction:Doose Syndrome is a myoclonic-atonic seizure disorder most prominent in the pediatric population. Several common genetic mutations have been identified. However, SUOX gene mutations have not yet been correlated with Doose Syndrome.Case Report:At the age of 5, the patient presented with absence seizures followed by the development of generalized tonic-clonic and myoclonic-atonic seizures. She was diagnosed with Doose Syndrome based on her clinical presentation and EEG findings. An MRI found an incidental left choroidal fissure cyst. Multiple medical interventions failed to control seizures. To date, the patient has shown partial response to clobazam (40 mg/day), phenobarbital (97.5 mg/day), and a ketogenic diet.Conclusion:SUOX gene defects have been associated with isolated sulfite oxidase deficiency. However, our patient did not have the typical presentation, progression, and symptomology of this disorder. Instead, several possible sources for the seizures were identified; the mutation itself, focal seizures originating from the brain lesion which then generalizes mimicking Doose Syndrome, or a synergistic role between the cyst and genetic mutation.
Keywords: Epilepsy; Genetics; Doose Syndrome; Myoclonic-Atonic Seizures